2007
DOI: 10.1002/ajmg.a.31837
|View full text |Cite
|
Sign up to set email alerts
|

A novel microdeletion at 16p11.2 harbors candidate genes for aortic valve development, seizure disorder, and mild mental retardation

Abstract: Many multiple congenital anomalies (MCA) are caused by recombination between homologous segmental duplications. In this report, we describe a novel “de novo” microdeletion in male monozygotic twins presenting with aortic valve abnormality, seizure disorder, and mild mental retardation. Using array based comparative genomic hybridization, we mapped the microdeletion to the short arm of chromosome 16 at 16p11.2 and refined it using hemizygosity mapping to about 593 kb, a region that overlaps with 24 genes. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
113
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 32 publications
6
113
1
2
Order By: Relevance
“…10 Similarly, the recurrent 16p11.2 microdeletion/duplication has been associated with autism and psychiatric disorders 7 and was linked earlier to mild MR, with seizures and abnormalities of the aortic valve. 11 The findings described above led us to investigate further the segregation of a microdeletion of 15q13.3, similar to the critical region involved in MR, identified in a family in which three boys were all affected with autism. The results of these studies, together with detailed clinical information, are presented and the genotype -phenotype correlation in this family is compared with those in the individuals described by Sharp et al 8 …”
Section: Introductionmentioning
confidence: 99%
“…10 Similarly, the recurrent 16p11.2 microdeletion/duplication has been associated with autism and psychiatric disorders 7 and was linked earlier to mild MR, with seizures and abnormalities of the aortic valve. 11 The findings described above led us to investigate further the segregation of a microdeletion of 15q13.3, similar to the critical region involved in MR, identified in a family in which three boys were all affected with autism. The results of these studies, together with detailed clinical information, are presented and the genotype -phenotype correlation in this family is compared with those in the individuals described by Sharp et al 8 …”
Section: Introductionmentioning
confidence: 99%
“…1 The estimated population prevalence is 0.5%, 2,3 with a prevalence of 0.3-0.7% in large cohorts of patients with intellectual disability and other developmental and behavioral problems. 4 The 16p11.2 microdeletion syndrome was initially described in patients from several developmental backgrounds, including developmental delay and mild cognitive impairment, 5 Asperger syndrome, 6 autism spectrum disorder, 2,7 dyslexia, 2 and individuals with aggression, hyperactivity, schizophrenia, bipolar disorder, and symptoms of obsessive-compulsive disorder. 7 More recently, the 16p11.2 microdeletion phenotype was broadened to include speechlanguage impairment, 1,4,8 motor delay, dysmorphologies, and seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, further studies have revealed that CNVs at this locus are responsible for ~1% of all ASD diagnoses, making it the most common CNV to be associated with ASD identified to date [13]. The 16p11.2 locus is flanked by two directly repeated segmental duplications of ~145 kb, which mediate the NAHR that results in the loss or gain of ~600 kb intermediate region containing ~27 protein-coding genes [9,12,40].…”
Section: Asd Associated With Cnvs On Chromosome 16p112mentioning
confidence: 99%
“…Thus, schizophrenia and autism might reflect mirror traits of the opposing extremes of behavioral phenotypes reflecting evolution of the social brain [43]. The phenotypes caused by CNV at the 16p11.2 locus are extremely heterogeneous, and, in addition to ASD, they have been reported to include metabolic disorders [44][45][46][47], cardiac anomalies [40,48], depressive disorder [49], speech delay [50], mental retardation [40,51,52], vertebral anomalies [52], syringomyelia [53], abnormal head size [36], and epilepsy [36,40], as well as other various congenital anomalies and behavioral abnormalities [44]. As the phenotypes of many more patients harboring CNVs in this genomic region are delineated, the full phenotypic spectrum associated with this locus will likely become more well-defined, and the critical genomic interval and dosage-sensitive genes responsible for the phenotypes will be determined.…”
Section: Asd Associated With Cnvs On Chromosome 16p112mentioning
confidence: 99%